PENERAPAN SISTEM HIBRID SOLAR PV-DIESEL SEBAGAI LANGKAH AWAL UNTUK MENINGKATKAN RASIO ELEKTRIFIKASI PEDESAAN - Dwinanto, Matheus M.; Koehuan, Verdy A.; Goetha, Selfiana; Sundari, Woro (Universitas Mataram, 2024)
Niskolen Hamlet, Tuapanaf Village is one of the hamlets in Takari District, Kupang Regency, East Nusa Tenggara Province that does not yet have access to electricity from the PLN network. Its residents work as farmers and ranchers but have not been able to meet their electricity needs independently. This activity is an initial step to reveal the benefits of installing a hybrid power plant (solar PV - Diesel generator) on the rural electrification ratio. The method used in this activity is the application of a hybrid power plant (solar PV - Diesel generator) in several homes of residents categorized as underprivileged families. The results obtained from this community service activity are that the existence of a hybrid power plant has helped underprivileged families to obtain electricity so that it is hoped that it can encourage development and economic growth which can ultimately improve the welfare of residents. In addition, with the availability of electricity, it will increase opportunities for reading and learning, improve health, and have a good influence on family planning (because at night it can be filled with social activities, and make it easier and faster for residents to obtain information from electronic media) and can increase the confidence of residents so that it can open the way for the development of various innovations and village entrepreneurship.